Diagnostic and therapeutic challenges in dense deposit disease: case report - Anand Prasad; Dhruv Jain; Navya Jaiswal; Harsha Shahi (Počki)
We report a complex case of a 15-year-old girl initially diagnosed with post-streptococcal glomerulonephritis (PSGN) but later identified as having dense deposit disease, which was initially classified as type 2 membranoproliferative glomerulonephritis. PSGN and C3 glomerulopathy present overlapping clinical and histological features, complicating diagnosis and treatment. This report highlights the case of a young patient whose initial presentation and management for PSGN transitioned to a complex diagnosis of dense deposit disease, necessitating tailored therapeutic interventions.